Memoirs and selected letters - Grant, Ulysses S. 1822-1885 (New York : The library of America, 1990)
Personal memoirs of U. S. Grant.
Selected letters 1839-1865.
Contenido : <Personal memoirs of U. S. Grant> <Selected letters 1839-1865>
Keywords: ESTADOS UNIDOS; LITERATURA AMERICANA USA; CARTAS; CAJA 2